Kemampuan berpikir kritis siswa madrasah dalam pembelajaran matematika melalui model pembelajaran Problem based Learning (PBL) di lembaga pendidikan Islam - Habib Husnial Pardi, Habib Husnial Pardi; Khafifaturrahmi, Khafifaturrahmi (Mathematic Education Departement, State Islamic University of Mataram, 2021)
This study aims to determine the effect of the Problem based learning model on students' critical thinking skills at MTs Ittihadul Bayan. The research method used is an experiment with a quasi-experimental design, namely a nonequivalent control group design. Sampling was taken by purposive sampling with a sample of 20 students for the control class and 24 students for the experimental class. The data collection technique used a test technique with a test instrument in the form of a description. The hypothesis in this study is that there is an effect of the Problem based Learning model on students' critical thinking skills in MTs. Ittihadul Bayan. The data analysis used is the t test, from the two groups the t count value is 2.897 with a df of 42 and a significance level of 5% so that the t table value is 1.681 so 2.897 > 1.681. With the results of the data analysis, the hypothesis proposed in this study is Ha is accepted and H0 is rejected, this shows that there is an effect of the Problem based Learning model on students' critical thinking skills in MTs Ittihadul Bayan.